The effect of intrinsic and extrinsic quality on the willingness to pay for a convenient meal: A combination of home-use-test with online auctions - Garrido, Dolores (2021)
A sensory evaluation using a home-use-test (HUT) setting and experimental online auctions at three storage times, were used to elicit willingness to pay (WTP) for two samples of ready meals with extended shelf life, one using microwave assisted pasteurization system (MAPS) and the other using freezing. The effect of the information on the name of a new technology and the environmental impacts associated with each technology was also measured. We found that sensory characteristics of the ready meal are the key drivers for subjects' WTP. Considering the specific context of this study, we did not find evidence that the name of the technology and the information on the environmental impacts associated with each technology impacted participants' WTP.